Early diagnosis by antigen test kit and early treatment by antiviral therapy: An ambulatory management strategy during COVID-19 crisis in Thailand. Issue 30 (29th July 2022) - Sayabovorn, Naruemit; Phisalprapa, Pochamana; Srivanichakorn, Weerachai; Washirasaksiri, Chaiwat; Auesomwang, Chonticha; Sitasuwan, Tullaya; Tinmanee, Rungsima; Chayakulkeeree, Methee; Phoompoung, Pakpoom; Mayurasakorn, Korapat; Sookrung, Nitat; Tungtrongchitr, Anchalee; et al.
Abstract : This study aimed to assess the clinical characteristics of patients who registered at the Siriraj Favipiravir Clinic and to share our experiences in this comparatively unique clinical setting. This retrospective study included patients who registered at the Siriraj Favipiravir Clinic during August 11, 2021 to September 14, 2021. Included adult patients were those with severe acute respiratory syndrome coronavirus 2 (coronavirus disease 2019 [COVID-19]) infection confirmed by antigen test kit (ATK) or real-time reverse transcription-polymerase chain reaction, no favipiravir contraindication, no prior COVID-19 treatment, and not receiving care from another medical facility. Demographic data and outcomes were collected and analyzed. Of the 1168 patients (mean age: 44.8 ± 16.4 years, 55.7% female) who registered at the clinic, 117 (10%) did not meet the treatment criteria, and 141 (12%) patients did not pick up their medication. One-third of patients had at least 1 symptom that indicated severe disease. Higher proportion of unvaccinated status (56.7% vs 47.5%, P = .005), higher proportion of persons with risk factors for disease progression (37.7% vs 31.3%, P = .028), and longer duration between the date of clinic registration and the date of positive diagnostic test (3 vs 2 days, P = .004) were significantly more commonly observed in the severe disease group compared to the nonsevere disease group. The duration between symptom onset and the date of clinic registration was significantly longer in the real-time reverse transcription-polymerase chain reaction group than in the ATK group (6 vs 4 days, P < .001). Most patients (90.0%) had completed favipiravir treatment regimen. The improvement and mortality rates were 86.7% and 1.2%, respectively. COVID-19 severity is associated with vaccination status, baseline risk factors, and timing between disease detection and treatment. The use of ATK influences patients to seek treatment significantly earlier in ambulatory setting. Our early diagnosis and antiviral treatment strategy yielded favorable results in an outpatient setting during a COVID-19 outbreak in Thailand.